Effect of soil conservation on productivity and food security on maize farmers in northwest Nigeria - Oladimeji, T.E. (Ahmadu Bello University, 2019)
The adoption of soil conservation practices is important for sustaining Nigerian agriculture where smallholder maize farmers face constraints such as low soil fertility that lead to low productivity and food insecurity. This study aims to analyze the effect of soil conservation on productivity and food security of maize farmers in Northwest Nigeria. The study used a two year panel data of 792 maize farmers for 2016 and 2017 cropping seasons, collected by IITA under “Taking Maize Agronomy to Scale in Africa (TAMASA)” project implementation in Nigeria. Descriptive statistics, pooled multivariate probit, random-effects ordered probit model, and fixed-effect regression were used to analyze the data collected. Result revealed that the average age of farmers was 44 years, average household size was 9 persons, average farming experience was 19 years, 75% of the farmers had no extension contact, 77% had no access to credit, 69% belong to no association, 81% had no access to maize contract farming, average livestock owned was 2.14 units, and average farm size was 3.23 hectares. Result showed that animal manure had the highest rate of adoption with 76% and 69% adoption rate in 2016 and 2017 cropping seasons respectively. There is significant correlation between soil conservation practices, suggesting that adoptions of the practices are interrelated. The unconditional and conditional probabilities of soil conservation practices revealed the existence of possible complementarities and substitutability among the practices. Majority of the farmers combined the adoption of two practices with adoption rates of 33% and 29% in 2016 and 2017 cropping seasons respectively, of which the combination of animal manure and crop residue retention was the major combined practices with 58% and 35% adoption rate in 2016 and 2017 cropping seasons respectively. Result showed that adoption of soil conservation practices was significantly influenced by factors such as age of household head, access to maize contract farming, livestock ownership, farming experience, access to off-farm income, access to credit, inorganic fertilizer, periods of weeding, and amount of rainfall. Also, the intensity of adoption of soil conservation practices were significantly influenced by factors such as access to maize contract farming, livestock ownership, farm size, access to off-farm income, inorganic fertilizer, periods of weeding, and amount of rainfall. The fixed effect regression result showed that practicing organic manure had significant effect on maize productivity and households’ food security.